Effectiveness and Safety of Intrathecal Ziconotide: Interim Analysis of the Patient Registry of Intrathecal Ziconotide Management (PRIZM). Issue 2 (14th July 2017) - Deer, Timothy; Rauck, Richard L.; Kim, Philip; Saulino, Michael F.; Wallace, Mark; Grigsby, Eric J.; Huang, I‐Zu; Mori, Fannie; Vanhove, Geertrui F.; McDowell, Gladstone C.
Abstract: Background: The Patient Registry of Intrathecal Ziconotide Management (PRIZM) evaluated long‐term effectiveness, safety, and tolerability of intrathecal ziconotide treatment in clinical practice. Methods: Patient Registry of Intrathecal Ziconotide Management was an open‐label, long‐term, multicenter, observational study of adult patients with severe chronic pain. This interim analysis (data through July 10, 2015) of ziconotide as the first vs. not first intrathecal agent in pump included change from baseline in the Numeric Pain Rating Scale (NPRS; primary efficacy measure) and Patient Global Impression of Change (PGIC) scores. Results: Enrollment closed at 93 patients; data collection was ongoing at the time of this interim analysis. Fifty‐one patients (54.8%) received ziconotide as the first agent in pump (FIP+), whereas 42 (45.2%) did not (FIP−). Mean (SD) baseline NPRS scores were 7.4 (1.9) and 7.9 (1.6) in FIP+ and FIP− patients, respectively. Mean (SEM) percentage changes in NPRS scores were −29.4% (5.5%) in FIP+ patients ( n = 26) and +6.4% (7.7%) in FIP− patients ( n = 17) at month 6 and −34.4% (9.1%) in FIP+ patients ( n = 14) and −3.4% (10.2%) in FIP− patients ( n = 9) at month 12. Improvement from baseline, measured by PGIC score, was reported in 69.2% of FIP+ ( n = 26) and 35.7% of FIP− ( n = 14) patients at month 6 and 85.7% of FIP+ ( n = 7) and 71.4% of FIP− ( n = 7) patients at month 12. The most common adverse events (≥ 10% of patients overall as of the data cut) were nausea (19.6% vs. 7.1% of FIP+ vs. FIP− patients, respectively), confusional state (9.8% vs. 11.9%), and dizziness (13.7% vs. 7.1%). Conclusions: Greater improvements in efficacy outcomes were observed when ziconotide was initiated as first‐line intrathecal therapy vs. not first intrathecal agent in pump. The adverse event profile was consistent with the ziconotide prescribing information.